PENERAPAN PRINSIP MAQASHID SYARIAH DALAM PERUNDANG-UNDANGAN DI INDONESIA - Muhammad Sofwan Jauhari (Karimiyah: Journal of Islamic Literature and Muslim Society, 2024)
Islamic law has a central position in the life of the majority of Indonesian society. Maqashid Sharia, the fundamental principles in Islamic law, became the main purpose of establishing law and became the foundation for the benefit of mankind. This study investigates the application of Maqashid Sharia in legislation through three research methods, namely normative, socio-legal, and literature legal research. The results showed a gap between theory and practice in the application of Maqashid Sharia. Although efforts have been made to integrate the principles of Maqashid Sharia in legislation, their implementation is limited and often influenced by local factors, madhhab, and socio-political context. As many as 40% of the public have a good understanding of Maqashid Sharia, while 60% of respondents, including judges and lawmakers, tend to interpret it according to the Shafi'i school. Therefore, serious efforts are needed in socialization, education, and integration of Maqashid Syariah in the legal system and law enforcement practices in Indonesia. This integration requires a systematic and measurable approach, where the textual approach provides a strong foundation of religious sources, the contextual approach ensures relevance and successful implementation, the participatory approach increases accountability and transparency, and the comparative approach allows the adoption of the best models from other countries